Study Package and Business Income of Coconut Oil Processing in The District of Kusambi, West Muna Regency - wati, erni; Rianda, La; Sakir, Sakir (Jurusan Ilmu dan Teknologi Pangan, Fakultas Pertanian,, 2020)
The objectives of this study are (1) to determine the availability and quantity of raw materials used in processing coconut oil; (2) to find out the skills of the workforce and the number of preparations produced in each time processing coconut oil; (3) to determine the productivity of coconut oil. The data is processed using qualitative data to determine the study of coconut oil processing business while finding out the amount of income using the R / C Ratio formula and to find productivity using the output/input formula. The population in this study were all coconut oil processing businesses. The total income of all coconut oil processing businesses in Kusambi District, West Muna Regency is Rp. 44,955,330 with an overall average of Rp. 6,916,205. While the average production productivity of the whole is Rp. 1.9088. Based on the calculation of the R / C ratio of coconut oil processing business, it is profitable Produk Innovation.